Effects of onabotulinum toxin type A injections in patients with Meige's syndrome - Duarte, Alexia; Coutinho, Léo; Germiniani, Francisco Manoel Branco; Teive, Hélio Afonso Ghizoni (Arquivos de Neuro-Psiquiatria, 2024)
Background Meige's syndrome is a type of facial dystonia characterized by the simultaneous occurrence of blepharospasm and oromandibular dystonia. Although botulinum toxin type A (OBTA) injections are the standard treatment, evidence of their effectiveness and safety in this scenario is still lacking.Objective Our research aimed to evaluate the improvement and occurrence of side effects following injections of onabotulinum toxin type A (OBTA) in patients with Meige's syndrome.Methods Patients with Meige's syndrome undergoing botulinum toxin injections were enrolled in this study. We assessed dystonia intensity before and 14 days after OBTA injection using the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) to measure the response of symptoms in the eyes (blepharospasm) and mouth (oromandibular dystonia). Other variables, such as dosage, side effects, and demographic data, were also recorded.Results The study included 41 participants, with a mean age of 67.7 years and a female-to-male ratio of 3.5:1. The mean BFMDRS score before the injections was 8.89, and after 14 days, it was 2.88. The most reported side effect was ptosis, with a 7.3% incidence. OBTA significantly reduced dystonia severity (p < 0.0001). The clinical response for the blepharospasm component was superior to the oromandibular dystonia component.Conclusion Our results support that OBTA seems to be an effective and safe therapeutic option for treating Meige's syndrome. The effect of OBTA was more pronounced in the treatment of blepharospasm than in oromandibular dystonia.
Keywords: Meige Syndrome; Dystonia; Movement Disorders; Botulinum Toxins